Cooking for one - Fisher, Jennifer (Recipe developer) (--For dummies., 2023)
"Cooking For One For Dummies is full of recipes to inspire you to create delicious meals, without packing your fridge full of forgotten leftovers. Learn to make mug cakes in the microwave, teriyaki salmon, and everything in between, with easy-to-follow instructions. We also cover cooking basics, so you can build your skills and wow the person whose opinion matters most--you. Stock up on kitchen tools you need to home-chef successfully, figure out healthy grocery shopping for one, and follow dozens of fantastic recipes. It's fun, it's delicious, it's healthy, and it's efficient. Let's start cooking for one."--Amazon.com.